Hidroenergetski sistemi - Biluš, Ignacijo (University of Maribor Press, 2024)
Hydropower Systems. The publication deals with hydropower systems. In the introduction, the basic characteristics of energy supply in Slovenia are given, and then renewable energy sources and hydropower are presented. This is followed by chapters on hydrology and hydropower, where basic hydro power plants clasification is given with their operation presentation. The energy parameters of water turbines are also discussed at the integral level. Separate chapters discuss conventional water turbines and their operating characteristics. The last chapter deals with the phenomenon of cavitation in water turbines. Cavitation characteristics are defined according to the type of water turbine and the impact of this phenomenon on the operation.